2007
DOI: 10.1080/08039480701643464
|View full text |Cite|
|
Sign up to set email alerts
|

EMDR treatment for children with PTSD: Results of a randomized controlled trial

Abstract: The objective of the study was to examine the efficacy of EMDR treatment for children with post-traumatic stress disorder (PTSD) compared with untreated children in a waiting list control group (WLC) participating in a randomized controlled superiority trial (RCT). Thirty-three 6-16-year-old children with a DSM-IV diagnosis of PTSD were randomly assigned to eight weekly EMDR sessions or the WLC group. The Posttraumatic Stress Symptom Scale for Children (PTSS-C scale) was used in interviews with children to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 30 publications
3
66
0
1
Order By: Relevance
“…In addition, studies have shown that EMDR is superior to psychoeducation [17], and produced significant changes in the brain through functional brain image research [18]. Previous research has examined the efficacy of EMDR treatment for children with PTSD compared with untreated children in a waiting list control group participating in a randomized controlled superiority trial, reporting that the EMDR group showed significantly greater alleviation of PTSD-related symptoms compared with the waiting list control group [19]. Bae et al [20] reported the potential application of EMDR for treating depressive disorders related not only to trauma but also to stressful life events.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, studies have shown that EMDR is superior to psychoeducation [17], and produced significant changes in the brain through functional brain image research [18]. Previous research has examined the efficacy of EMDR treatment for children with PTSD compared with untreated children in a waiting list control group participating in a randomized controlled superiority trial, reporting that the EMDR group showed significantly greater alleviation of PTSD-related symptoms compared with the waiting list control group [19]. Bae et al [20] reported the potential application of EMDR for treating depressive disorders related not only to trauma but also to stressful life events.…”
Section: Introductionmentioning
confidence: 96%
“…These include Trauma-Focused CBT (TF-CBT; Cohen, Deblinger, Mannarino & Steer, 2004), Eye Movement Desensitization and Reprocessing (EMDR; Ahmad, Larsson, & Sundelin-Wahlsten, 2007), Stress Inoculation Training (Vickerman & Margolin, 2009), and cognitive therapy (P. Smith et al, 2007). TF-CBT has the strongest evidence base for the treatment of pediatric PTSD (Silverman et al, 2008).…”
mentioning
confidence: 99%
“…One randomized controlled trial among children involved in road traffic accidents showed no effect for PD provided 4 weeks after the accident [16], a finding that is consistent with earlier adult research [17]. Empirical support for EMDR as an effective early intervention for ASD in children is currently lacking, but the approach appears promising for children with chronic PTSD [18][19][20][21][22]. A recent Cochrane review on psychological treatment for PTSD in adults shows favourable results for EMDR [23].…”
Section: Introductionmentioning
confidence: 61%
“…However, if intrusive memories, flashbacks and nightmares are prominent, a combination of TF-CBT and EMDR could make a promising intervention for reducing acute stress reactions. EMDR appears to have very strong effects on intrusions and distressing memories [18]. Besides the primary benefit of EMDR being effective, the procedure is also efficient, requiring only 3-5 hours of treatment, in the case that the traumatic memory is related to a single event.…”
Section: Discussionmentioning
confidence: 99%